Enabling sustainable shrimp aquaculture: Narrowing the gaps between science and policy in Thailand - Dao Huy Giap (2018)
Since the early 1980s, shrimp aquaculture has expanded rapidly with production increasing more than 100-fold from 31,000 t in 1976 to 2.6 million tons in 2006 (Fig. 7.1). About 90% of farmed shrimp is produced in Asia (mainly in China, Thailand, Vietnam, Indonesia and India). The other 10% is produced mainly in Latin America, where Mexico, Brazil and Ecuador are the largest producers (Fig. 7.1). The two main aquaculture species that are farmed - black tiger shrimp (Penaeus monodon) and Pacific white shrimp (Penaeus vannamei) - accounted for about 88% of the shrimp in the aquaculture industry in 2006. Today, almost half of the shrimp eaten is grown in tropical developing countries in coastal ponds and traded to be eaten in restaurants and homes in temperate industrialized countries. Thailand and Vietnam are the largest exporters, while much of China's growing production is consumed domestically. The Europe, US, and Japan are the largest importers, together comprising 80-91% of total global import volumes each year between 1976 and 2006 (Fig. 7.2). © 2010 Springer Science+Business Media B.V.